Utilization of Pentanol as Biofuels in Compression Ignition Engines - No, Soo-Young (Frontiers in Mechanical Engineering, 2020)
Of several higher alcohols such as pentanol, hexanol, octanol, decanol, dodecanol, phytol, fusel oil etc., pentanol isomers have recently received remarkable attention as alternative fuels for diesel engines because they emit less greenhouse gases and harmful pollutants. Because of great potential as a blending component and physico-chemical properties of pentanol, binary blends such as diesel/pentanol and biodiesel/pentanol and ternary blends such as diesel/biodiesel /pentanol were mainly studied in the conventional diesel engine. Quaternary blends of diesel, biodiesel, straight vegetable oil, and pentanol was also investigated. Very few information related to the application of pentanol to advanced CI engine is available in the literature. The diesel/pentanol blends coupled with EGR technology could simultaneously reduce NOx and soot emissions from CI engine. Further, diesel/pentanol blends generally produced higher CO and HC emissions than diesel fuel. However, CO and HC emissions were significantly reduced by mixing the cetane improver with the blends. Up to 45% 50% n-pentanol/diesel blends can be safely used in diesel engines without any engine modification or any additive. However, in terms of kinematic viscosity, lubricity, and oxidation stability of diesel/pentanol blends, the use of pentanol should be limited to concentrations below 10%. Generally, in the studies of biodiesel/pentanol blends in CI engines, the reduction of CO, HC, NOx and smoke emissions were observed compared to neat biodiesel. For ternary blends, diesel/biodiesel/pentanol blends were mainly investigated by the researchers. The emission characteristics in terms of CO, HC, NOx and smoke opacity showed the different trend according to the pentanol proportion in the ternary blends, particularly less than 10% or more than 10%. To increase the biofuels in CI engine, more studies for the quaternary blends of pentanol are required..